Geographic information science : 9th International Conference, GIScience 2016, Montreal, QC, Canada, September 27-30, 2016, Proceedings /: 9th International Conference, GIScience 2016, Montreal, QC, Canada, September 27-30, 2016, Proceedings. (2016) - Unknown
No abstract available